Diabetes Self-Management and Distress Levels in Patients With Diabetes Mellitus: a Cross Sectional Study - Rahmad Wahyudi; Nisfil Mufidah; Sabila Firdausita (Universitas Muhammadiyah Yogyakarta, 2022)
Background: Patients suffer Diabetes Mellitus face challenges related care management disease, treatment proper self. Distress condition covers passionate stretch, enthusiastic and behavioral challenges consequence burden management self. Objective: The aim of the think about to analyze the relationship between Diabetes Self-Management and trouble Levels in Diabetes Mellitus patients. Methods: The study used analytic correlation through a cross-sectional approach. Diabetes self-management was variable free and trouble level was variable subordinate. Taking a test of 55 patients utilizing the purposive examining strategy method at Wound Center Madura with criteria inclusion, DM type 1 and 2 patients were undergoing care wounds with ulcer diabetes. Distress instruments used Diabetes Distress Scale and Diabetes Self-Management survey. This ponder utilized the Spearmen rank relationship test. Results: The measurable test comes about appear p-value = 0.000 a = 0.05. showing that there is a connection between diabetes self-management with distressed diabetes patients at Wound Center Madura, Indonesia. Nearly half of diabetes patients have a high level of distress, high emotional burden, indicating a high personal emotional burden in the patient, such as feeling tired in dealing with various disease management. This personal reaction can lead to feelings of fear, anger because of diabetes mellitus, while the behavior of checking blood sugar independently with diabetes self management control.Conclusion: The goal of Diabetes Self-Management is to be able to reduce the Distress and control diabetes mellitus, while poor Diabetes Self-management controls a risk of complications and tends to feel worried and frustrated because they feel unable to control diabetes.